60‐2: Contact Model Analysis of GaN‐Based Micro Light‐Emitting Diodes (MicroLEDs) with Distinct Structures and Bonding Pads. Issue 1 (28th June 2021) - Liu, Yibo; Zhang, Ke; Feng, Feng; Chan, Ka-Wah; Liu, Zhaojun; Kwok, Hoi Sing
Abstract : In this paper, the contact model analysis based on gold (Au) and aluminum (Al) with distinct structures and bonding pads of GaN‐based Micro‐LED was proposed. Firstly, the fabrication process and three different structures (testing, bottom emitting and top emitting structures) with 30 −200µm size were introduced. Then, the electrical properties of testing structure were analyzed by extracting the series resistances and ideality factors. Next, the performances of two metals with bottom and top emitting structures were evaluated electrically and optically throughout the injection current at forward bias, leakage current at reverse bias, radiometric power and luminous flux. The final results indicated Au contact is superior to Al for the indium bonding pads on Micro‐LEDs.